The Challenge of Youth Employment in Sri Lanka - Gunatilaka, Ramani; Mayer, Markus; Vodopivec, Milan (World Bank, 2012)
Sri Lanka has been regarded as a model of a country with successful social policies, yet for decades it has faced major challenges in providing employment and satisfying other aspirations of youth. Although the labor force has become more educated, and this trend is particularly marked for youth, the main source of employment for both youth and adults remains the informal sector. Moreover, the importance of the informal sector as a source of employment has increased since the mid-1990s. On the positive side, unemployment declined in last decades, particularly for youth. The Sri Lankan government has continually acted on various fronts to address the youth unemployment problem. It has tried to improve and modernize Sri Lanka's general education system, which has long been criticized as too academic, and to increase the accessibility of training so as to promote the employability youth leaving school. Other actions included strengthening entrepreneurship programs and introducing career guidance and counseling and improving labor market information to help young people in their job searches and to guide human resource planning. In 2007, the government developed the National Action Plan for youth employment, built, for the first time, on a coherent youth employment policy framework and deriving an encompassing and consistent set of policy recommendations. The plan was based on in-depth analysis of Sri Lanka's labor market, provided via a series of background papers undertaken under the auspices of the Youth Employment Network (YEN). To provide the richness and comprehensiveness of this analysis in its totality, these papers, updated and revised, are collected in the present book. This book offers a wealth of valuable advice to the government and other stakeholders to achieve this goal. By exploiting the full potential of the youth, not only will their talent, aspirations, and energy be harnessed to advance economic growth, but also the existing inequities will be reduced and, hopefully in the longer run, eliminated.